The Human Cathelicidin Antimicrobial Peptide LL-37 and Mimics are Potential Anticancer Drugs - Kuroda, Kengo; Okumura, Kazuhiko; Isogai, Hiroshi; Isogai, Emiko (Frontiers in Oncology, 2015)
Antimicrobial peptides (AMPs) play a critical role in innate host defense against microbial pathogens in many organisms. The human cathelicidin LL-37 has a net positive charge and is amphiphilic, and can eliminate pathogenic microbes directly via electrostatic attraction toward negatively charged bacterial membranes. A number of studies have shown that LL-37 participates in various host immune systems, such as inflammatory responses and tissue repair, in addition to its antibacterial properties. Moreover, recent evidence suggests that it is also involved in the regulation of cancer. Indeed, previous studies have suggested that human LL-37 is involved in carcinogenesis via multiple reporters such as FPR2 (FPRL1), EGFR, and ERBb2, although LL-37 and its fragments and analogues also show anticancer effects in various cancer cell lines. This discrepancy can be attributed to peptide-based factors, host membrane-based factors, and signal regulation. Here, we describe the association between AMPs and cancer with a focus on anticancer peptide functions and selectivity in an effort to understand potential therapeutic implications.